2005
DOI: 10.1213/01.ane.0000150610.44631.9d
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Blood Transfusions and Delayed Wound Healing After Hip Replacement Surgery: Effects on Duration of Hospitalization

Abstract: Patients who receive allogeneic blood transfusions after orthopedic surgery have a longer duration of hospitalization, and this cannot be explained by a more frequent incidence of infections in transfused patients. To determine whether transfusion of allogeneic blood interferes with wound healing and therefore increases the duration of hospitalization, we performed an observational study in 444 consecutive patients scheduled for elective primary hip surgery. Transfusion, wound, and infection variables were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
1
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(124 citation statements)
references
References 21 publications
4
104
1
15
Order By: Relevance
“…al. find a longer healing process after usage of allogeneic blood transfusion, compared to a control group in which patients did not receive allogeneic blood transfusion (Weber et al, 2005).…”
Section: Washed Autologous Transfusionmentioning
confidence: 69%
See 2 more Smart Citations
“…al. find a longer healing process after usage of allogeneic blood transfusion, compared to a control group in which patients did not receive allogeneic blood transfusion (Weber et al, 2005).…”
Section: Washed Autologous Transfusionmentioning
confidence: 69%
“…The effect of hospital admission time has been made clear by Weber et al who described an increase of hospital admission time of 2.7 days (+/-0.5 days) per transfused unit of red blood cells in total hip arthroplasty patients (Weber et al, 2005). In a study we performed in 1,422 patients who received a total hip arthroplasty, we found the administration of allogeneic blood to be one of the independent variables in a stepwise regression analysis, for ASA-Classes: I: healthy individuals; II: patients with a mild systemic defect, without functional impairment; III: patients with a seriously impairing systemic defect; IV: patients with a systemic defect that poses a constant threat for life; V: patients who are moribund and who will, with or without operation, probably die within 24 hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Allogenic blood transfusion may prolong the duration of hospital stays 5 and may adversely affect the outcomes of surgical patients by increasing the risk of surgical site infection and periprosthetic joint infection 6,7 . Therefore, great effort has been made to reduce the rate of allogenic blood transfusion by implementing various blood conservation strategies to reduce perioperative blood loss 4 .…”
mentioning
confidence: 99%
“…A segurança do tratamento em estudo foi analisada por meio da perda sanguínea, que foi avaliada através dos seguintes critérios: a) queda de 2g/dl ou mais dos níveis de hemoglobina (Hb) do pré-operatório em relação ao pós (15)(16) ; b) necessidade de duas ou mais unidades de concentrado de hemácias (CHAD) (43)(44)(45)(46) . No grupo RIV, 14 pacientes necessitaram de transfusão de duas ou mais unidades de CHAD no pós-operatório; no grupo ENO, 12 pacientes necessitaram de transfusão de duas ou mais unidades de CHAD.…”
Section: Métodosunclassified